Unique structure of ozoralizumab, a trivalent anti-TNFα NANOBODY® compound, offers the potential advantage of mitigating the risk of immune complex-induced inflammation - Kyuuma, Masanao; Kaku, Ayaka; Mishima-Tsumagari, Chiemi; Ogawa, Bunichiro; Endo, Mayumi; Tamura, Yunoshin; Ishikura, Kei-ichiro; Mima, Masashi; Nakanishi, Yutaka; Fujii, Yasuyuki (Frontiers in Immunology, 2023)
Biologics have become an important component of treatment strategies for a variety of diseases, but the immunogenicity of large immune complexes (ICs) and aggregates of biologics may increase risk of adverse events is a concern for biologics and it remains unclear whether large ICs consisting of intrinsic antigen and therapeutic antibodies are actually involved in acute local inflammation such as injection site reaction (ISR). Ozoralizumab is a trivalent, bispecific NANOBODY® compound that differs structurally from IgGs. Treatment with ozoralizumab has been shown to provide beneficial effects in the treatment of rheumatoid arthritis (RA) comparable to those obtained with other TNFα inhibitors. Very few ISRs (2%) have been reported after ozoralizumab administration, and the drug has been shown to have acceptable safety and tolerability. In this study, in order to elucidate the mechanism underlying the reduced incidence of ISRs associated with ozoralizumab administration, we investigated the stoichiometry of two TNFα inhibitors (ozoralizumab and adalimumab, an anti-TNFα IgG) ICs and the induction by these drugs of Fcγ receptor (FcγR)-mediated immune responses on neutrophils. Ozoralizumab-TNFα ICs are smaller than adalimumab-TNFα ICs and lack an Fc portion, thus mitigating FcγR-mediated immune responses on neutrophils. We also developed a model of anti-TNFα antibody-TNFα IC-induced subcutaneous inflammation and found that ozoralizumab-TNFα ICs do not induce any significant inflammation at injection sites. The results of our studies suggest that ozoralizumab is a promising candidate for the treatment of RA that entails a lower risk of the IC-mediated immune cell activation that leads to unwanted immune responses.